2012
DOI: 10.5812/aapm.3599
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Intubation Without Use of Muscle Relaxants: Comparison of Remifentanil and Alfentanil

Abstract: My objective is to analyze the efficiency of remifentanil-propofol and alfentanil-propofol combinations for laryngoscopic endotracheal intubation in the absence of muscle relaxants. This analysis reviews the work by Imani et al. (1). Muscle relaxants are frequently used to facilitate endotracheal intubation during anesthesia induction. However, the administration of short-acting depolarizing muscle relaxants is closely related to postoperative myalgias, malignant hyperthermia, hyperkalemia, and increased intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Safavi M et al showed that some drugs such as Nitroglycerin are effective in attenuating the pressor response to tracheal intubation in severe preeclampsia and could be used instead of opioids to control hemodynamic responses (22). Remifentanil and fentanyl were also used effectively in endotracheal intubation without use of neuromuscular blocking drugs (23,24). Remifentanil infusion tends to faster wake up test than alfentanil in spinal fusion surgeries (25) (because of rapid metabolism) and is suggested to be used in situations that require fast effect and rapid recovery of opioid effects.…”
Section: Methodsmentioning
confidence: 99%
“…Safavi M et al showed that some drugs such as Nitroglycerin are effective in attenuating the pressor response to tracheal intubation in severe preeclampsia and could be used instead of opioids to control hemodynamic responses (22). Remifentanil and fentanyl were also used effectively in endotracheal intubation without use of neuromuscular blocking drugs (23,24). Remifentanil infusion tends to faster wake up test than alfentanil in spinal fusion surgeries (25) (because of rapid metabolism) and is suggested to be used in situations that require fast effect and rapid recovery of opioid effects.…”
Section: Methodsmentioning
confidence: 99%
“…Safavi M et al showed that some drugs such as Nitroglycerin are effective in attenuating the pressor response to tracheal intubation in severe preeclampsia and could be used instead of opioids to control hemodynamic responses ( 22 ). Remifentanil and fentanyl were also used effectively in endotracheal intubation without use of neuromuscular blocking drugs ( 23 , 24 ). Remifentanil infusion tends to faster wake up test than alfentanil in spinal fusion surgeries ( 25 ) (because of rapid metabolism) and is suggested to be used in situations that require fast effect and rapid recovery of opioid effects.…”
Section: Discussionmentioning
confidence: 99%